Just in time elements extraction and prioritization for health care unit using decision making approach. Issue 7 (5th August 2019) - Kaswan, Mahender Singh; Rathi, Rajeev; Singh, Mahipal
Abstract : Purpose: The purpose of this paper is to identify and prioritize prime just-in-time (JIT) elements in Indian healthcare sector based on the degree of importance and difficulty. This facilitates the implementation of JIT philosophy in healthcare services without any failure as well as provides quality services to patients at low cost. Design/methodology/approach: JIT elements related to health care services have been sorted out from comprehensive literature survey. Moreover, important and difficult JIT elements have been ranked on the basis of score obtained by the quantitative method using statistical tools. Furthermore, validation and prioritization of important JIT elements based on the degree of importance have been computed using the analytical hierarchy process (AHP) and best worst method (BWM). Findings: The present work provides important, difficult and easy to implement JIT elements in healthcare services. Besides, this work justifies the application of decision-making tool (AHP, BWM) for the prioritization of JIT elements in the health care sector. Practical implications: The present study develops a deep understanding of JIT concepts in health care services. Furthermore, it motivates professionals for implementing JIT in healthcare services with healthy situation for both hospital and supplier. Social implications: The present work is beneficial for all the dimensions of sustainable development (social, economic and environmental). The implementation of JIT with a proper understanding of its elements results in an improved patient care, lesser cost of healthcare delivery, time and better management of associated medical items. This work also facilitates the proper management of inventory items together with the reduction in various Lean wastes with the proper implementation of JIT in healthcare. The reduction in various associated wastes leads to cleaner surrounding and lesser environmental degradation. Originality/value: This paper outlines the need of a robust JIT approach in the healthcare sector for quality services. The efficacy of JIT, AHP and BWM has been explored to find out critical elements for successful JIT implementation in health care.